DEVELOPMENT OF FORMALIZED QUERIES FOR IDENTIFYING RELEVANT WEB FORUMS AND THREADS - Тимовчак-Максимець, О.; Пелещишин, А. (Proceedings of National Aviation University (archive), 2012)
The four ways of identifying web forums which are relevant to the object of target consumer experiencehave been examined. The peculiar features and appropriateness of applying each of the ways under variousconditions are shown. Method of identifying relevant communities in Web through employing facilities andresources of global search engines was studied. Two search queries to global search engines were developedand characterized in details.